Classroom Management as a Determinant of Teaching and Learning Effectiveness in Indonesia - Pangestika, Novita Widya (Journal of Educational Management and Strategy, 2025)
This study aims to investigate classroom management as a key determinant of teaching and learning effectiveness in Indonesia within the context of the Industry 5.0 era. Industry 5.0 emphasizes human-centered innovation and the synergy between human intelligence and technological advancement. The research explores how teachers’ management strategies—covering classroom organization, behavioral regulation, instructional design, and digital collaboration—affect students’ engagement, motivation, and learning outcomes. A mixed-methods approach was employed, integrating quantitative and qualitative analyses. Quantitative data were collected through questionnaires administered to teachers and students from various secondary schools, while qualitative data were obtained through structured interviews and classroom observations. The data were analyzed using correlation and regression tests to determine relationships among variables, complemented by thematic analysis for deeper interpretation. The findings reveal a significant positive correlation between effective classroom management and teaching-learning effectiveness. Classrooms that incorporate structured organization, participatory management, and technology-supported activities demonstrate improved student collaboration and academic performance. In the Industry 5.0 context, classroom management is not limited to administrative control but integrates digital literacy, emotional intelligence, and personalized learning to foster adaptability and innovation. The study concludes that effective classroom management serves as a strategic foundation for achieving sustainable educational quality and human-centered learning in Indonesian schools, aligning with the transformative demands of Industry 5.0.